2012
DOI: 10.1177/0897190012442715
|View full text |Cite
|
Sign up to set email alerts
|

Review of Survey Articles Regarding Medication Therapy Management (MTM) Services/Programs in the United States

Abstract: Despite the identified barriers to the provision of MTM services, pharmacists reportedly found it professionally rewarding to provide these services. Pharmacists claimed to have adequate clinical knowledge, experience, and access to information required to provide MTM services. Pharmacy students were of the opinion that the provision of MTM services was important to the advancement of the pharmacy profession and in providing patients with a higher level of care. Physicians supported having pharmacists adjust p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…A recent review of MM services (called medication therapy management [MTM] in the United States) found that the majority of patients surveyed were not aware of these services and many did not see a need for them. 11 In general, patients were not willing to pay out of pocket for MTM services in the United States. 11 In September 2010, the BC Ministry of Health and the BC Pharmacy Association introduced a pilot MM program, 12 and since its completion in January 2012, there has been province-wide implementation of several MM services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of MM services (called medication therapy management [MTM] in the United States) found that the majority of patients surveyed were not aware of these services and many did not see a need for them. 11 In general, patients were not willing to pay out of pocket for MTM services in the United States. 11 In September 2010, the BC Ministry of Health and the BC Pharmacy Association introduced a pilot MM program, 12 and since its completion in January 2012, there has been province-wide implementation of several MM services.…”
Section: Introductionmentioning
confidence: 99%
“…11 In general, patients were not willing to pay out of pocket for MTM services in the United States. 11 In September 2010, the BC Ministry of Health and the BC Pharmacy Association introduced a pilot MM program, 12 and since its completion in January 2012, there has been province-wide implementation of several MM services. 13 One of the most widely provided MM services is medication review, whereby the pharmacist interviews the patient to prepare a best-possible medication history, assesses the patient's medications for any DTPs, and then devises a care plan to resolve DTPs and evaluate results.…”
Section: Introductionmentioning
confidence: 99%
“…Typically provided to high-risk patients and independent of medication dispensing, MTM services include a comprehensive review of a patient’s current and past medication history and development of a medication-related action plan [5658]. By focusing on the patient’s complete medication therapy regimen, the pharmacist can assess various factors potentially causing medication-related problems.…”
Section: Introductionmentioning
confidence: 99%
“…The limited number of qualified practitioners for the delivery of CMM and the high demand of potential users of this service mean that specific groups of patients need to be prioritized. Many successful practice settings in the United States target patients that can benefit most from CMM services: individuals in use of several medications and who have multiple comorbidities [38]. The participants in this study also emphasized that prioritizing more complex patients for the service should be a strategy.…”
Section: Discussionmentioning
confidence: 98%